Role of Laparoscopy in Reproductive Age Group Women with Gynecological Problems in a Tertiary Medical College - Kayastha, Bhagirathi; Shrestha, Buddhi; Shrestha, Subha; Acharya, Manisha; Pradhan, Alok (Journal of College of Medical Sciences-Nepal, 2024)
Background Laparoscopy has been a revolution in gynecological surgery as it is safe and minimally invasive. It can be used as a diagnostic as well as treatment modality for different gynecological problems like Chronic pelvic pain, adnexal cyst, ectopic pregnancy, Pelvic inflammatory disease and infertility. Methods This study was carried out at College of Medical Sciences-Teaching Hospital from April 2022 to March 2023 in 105 women. All the women undergoing laparoscopic surgeries were analyzed for indications, intraoperative findings and interventions. Results The mean±SD of age of women was 30.34±7.73 years, most were in age group 26-35 years. The most common indications for Laparoscopy were for Adnexal cyst (74.28%), Chronic Pelvic Pain (14.28%) and Infertility (11.42%). The most common findings according to site were Ovarian pathology (48.60 %) followed by peritoneal pathology (22.9 %), Tubal pathology (17.14%) and normal findings (10.50%). In ovarian - Dermoid cyst (31.37 %), in tubal - ectopic pregnancy (55.56%), in peritoneal-Adhesions (45.83%) were the most common finding. In laparoscopic interventions, 26.70% had cystectomy, 14.3 % had salpingectomy and 13.3 % had Sterilization. Conclusions Laparoscopy as a modality for diagnosis and treatment of gynecological problems has been well established in recent times. It’s been a choice of surgery because of its reduce postoperative pain, shorter hospital stay, faster recovery and minimal scar. However, adequate advanced training and equipment are needed to perform skillful laparoscopic surgeries.